Variable effects of c-terminal fusions on FLS2 function: not all epitope tags are created equal - Hurst, Charlotte H.; Turnbull, Dionne; Keinath, Nana (Plant physiology, 2018)
Receptor-like kinases (RLKs) are the largest family of proteins in plants and are responsible for perceiving the vast majority of extracellular stimuli. Thus, RLKs function in diverse processes, including sensing pathogen attacks, regulating symbiotic interactions, transducing hormone and peptide signals, and monitoring cell wall status. However, despite their fundamental role in plant biology, very few antibodies are available against RLKs, which necessitates the use of epitope tags and fluorescent protein fusions in biochemical analyses such as immunoblot analysis and intracellular visualization. Epitope tags are widely used and are typically assumed to be benign, with no influence on protein function. FLAGELLIN SENSITIVE2 (FLS2) is the receptor for bacterial flagellin and often is used as a model for RLK function. Previous work implies that carboxyl-terminal epitope fusions to FLS2 maintain protein function. Here, a detailed complementation analysis of Arabidopsis (Arabidopsis thaliana) fls2 mutant plants expressing various FLS2 C-terminal epitope fusions revealed highly variable and unpredictable FLS2-mediated signaling outputs. In addition, only one out of four FLS2 epitope fusions maintained the ability to inhibit plant growth in response to flg22 treatment comparable to that in the wild type or control untagged transgenic lines. These results raise concerns over the widespread use of RLK epitope tag fusions for functional studies. Many of the subtleties of FLS2 function, and by extension those of other RLKs, may have been overlooked or inappropriately interpreted through the use of RLK epitope tag fusions.
Gesehen am 22.01.2020